Exploring the representation of the nature of science in science textbooks - Okan, Beyza. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
This study relies on the Reconceptualized Family Resemblance Approach to Nature of Science (RFN) (Erduran & Dagher, 2014a; Kaya & Erduran, 2016). The study aims to examine the representation of NOS in 5th, 6th, 7th and 8th-grade science textbooks. Also, exploring the science teachers’ perceptions of NOS, their textbook usage to teach NOS and their suggestions to integrate NOS in textbooks are another focus of the study. Four textbooks given to all middle school students freely by the Ministry of National Education of Turkey were analyzed through content analysis. Coding units which are sentences, steps of activities, etc. in the content, activity, and assessment sections of the textbooks were traced in the light of the keywords created by Kaya and Erduran (2016). Also, new keywords were generated during the analysis. Then, 8 science teachers were selected purposively, and semi-structured interviews were conducted. “NOS Questionnaire” developed by Kaya et al. (2019) was administrated to teachers. Thematic analysis and descriptive analysis were completed for analyzing data from interviews and questionnaire respectively. As a result of the textbook analysis, it was found that the textbooks do not explicitly represent the NOS, but scientific practices, social certification and dissemination, and professional activities are more emphasized in activities sections of all textbooks. But still, there is a need to integrate explicit references in the content sections of the textbooks. Teachers' perception and understanding of NOS, in general, were found high, but some teachers were found to have naive understandings of the scientific practices, methods and methodological rules, and professional activities. Almost all of the teachers stated that they do not use textbooks to teach NOS because the textbooks lack of including NOS adequately. They offered suggestions to include NOS in textbooks such as integration of the history of science, technology, questions, and activities to teach NOS explicitly. Overall, the study has implications for the integration of NOS holistically in science textbooks.
Keywords: Science -- Study and teaching -- Textbooks.